Seller's replenishment decision for material following quadratic demand with different payment structures. (2022) - Shaikh, Azharuddin; Mishra, Poonam; Talati, Isha
Abstract: The acquiring cost of any material is often paid by implementing one of the payment practice. Payment is either through cash or else an interest free credit period is availed or advance is given while placing an order. Each of this method has rewards and drawbacks associated with it. In realism, a payment structure which is an amalgamation of these three options is put to use. The present work deals with mathematical modelling of regulating the refilling plan for seller where items adhere to quadratic demand style. The seller acquires an advance-cash-credit payment form from the provider, while forwarding a similar concept of cash-credit to the consumers. For validating the model, numerical exemplar with suitable values of inventory parameters are discussed. Lastly, managerial insights are furnished, by investigating effect of inventory parameters in reference to alteration of one parameter at a time.